The Welfare Analysis of Oil Palm Smallholder Farmers in Pangkalan Banteng Sub-District, Central Kalimantan - Setyawan, Heri; Kurniawan, Indra; Setiawan, Koko; Listianto, Herry (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2020)
Oil palm is one of the plantation crops in Indonesia which has the fastest development compared to the other plantation crops, one of them is in the oil palm smallholder farmers sector. However, this development has not been completely and evenly distributed, so that the condition of oil palm plantations in the world is considered not in harmony with oil palm smallholder farmers in rural areas. The level of harmony can be measured based on the level of welfare of the existing oil palm smallholder farmers. The research objective was to determine the welfare of oil palm smallholder farmers in Pangkalan Banteng, Central Kalimantan. The methods used were a survey and direct field observation. The farmer who became the research respondents were selected using purposive sampling. The number of respondents was 100. The questionnaire was measured using the Likert scale. The results of the study showed that most of the oil palm farmers in Pangkalan Banteng were in a prosperous standard of living, as evidenced by the fact that oil palm farming was able to meet the consumption needs of all family members, the ownership of savings for the future, the ownership of valuable and durable goods, as well as able to provide social assistance and permanent home ownership. However, some farmer families were still below the prosperous category due to the low productivity of their farming and the small area of land they have, so their income was still low.